2015
DOI: 10.1093/treephys/tpu109
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of stomatal patchiness and its spatial scale in leaves from various sizes of trees distributed in a South-east Asian tropical rainforest in Peninsular Malaysia

Abstract: In this study, we demonstrated the occurrence of stomatal patchiness and its spatial scale in leaves from various sizes of trees grown in a lowland dipterocarp forest in Peninsular Malaysia. To evaluate the patterns of stomatal behavior, we used three techniques simultaneously to analyze heterobaric or homobaric leaves from five tree species ranging from 0.6 to 31 m in height: (i) diurnal changes in chlorophyll fluorescence imaging, (ii) observation and simulation of leaf gas-exchange rates and (iii) a pressur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
2
8
0
Order By: Relevance
“…A study by De Frenne et al (2013) on the moderating effect of microclimate on plant responses under macroclimate warming reported a buffering of understory vegetation from macroclimatic effects due to canopy closure and an induced climatic lag in this habitat (De Frenne et al, 2013). This suggestion is also supported by Kamakura et al (2018) who reported uniform stomatal behavior in leaves in the subcanopy or understory of a Malaysian lowland dipterocarp forest, and where stomatal patchiness in homobaric and heterobaric leaves in the understory environment was similar. They partially attributed the uniformity in stomatal conductance to the less pronounced environmental conditions of irradiance and VPD in the understory than those experienced in the canopy (Kamakura et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…A study by De Frenne et al (2013) on the moderating effect of microclimate on plant responses under macroclimate warming reported a buffering of understory vegetation from macroclimatic effects due to canopy closure and an induced climatic lag in this habitat (De Frenne et al, 2013). This suggestion is also supported by Kamakura et al (2018) who reported uniform stomatal behavior in leaves in the subcanopy or understory of a Malaysian lowland dipterocarp forest, and where stomatal patchiness in homobaric and heterobaric leaves in the understory environment was similar. They partially attributed the uniformity in stomatal conductance to the less pronounced environmental conditions of irradiance and VPD in the understory than those experienced in the canopy (Kamakura et al, 2018).…”
Section: Discussionsupporting
confidence: 76%
“…This suggestion is also supported by Kamakura et al (2018) who reported uniform stomatal behavior in leaves in the subcanopy or understory of a Malaysian lowland dipterocarp forest, and where stomatal patchiness in homobaric and heterobaric leaves in the understory environment was similar. They partially attributed the uniformity in stomatal conductance to the less pronounced environmental conditions of irradiance and VPD in the understory than those experienced in the canopy (Kamakura et al, 2018). Our observed trend in the understory-subcanopy g smax may reflect a fundamental difference in sensitivity to the effects of macroclimate between the open-canopy and the understory-subcanopy habitats, as classified in this study.…”
Section: Discussionsupporting
confidence: 76%
“…Both upper canopy and understory trees could have deep roots allowing access to deep soil water stores (Nepstad et al, 1994;Stahl, H erault et al, 2013). However, the typical microclimate conditions in the upper canopy layer are low air humidity, high air temperature, and high irradiance (Chazdon & Fetcher, 1984;Kamakura et al, 2015;Kumagai et al, 2001), all of which are aggravated during the dry season, especially in an El Niño year (Figure 2). Thus, the more upper canopy leaves are exposed to demanding atmospheric conditions, the more likely they are to exhibit a strong reduction of stomatal conductance and photosynthesis during drought, compared to understory trees (Sperlich et al, 2015).…”
Section: Stomatal Conductance As the Main Driver Of Photosynthesis mentioning
confidence: 99%
“…Patchy stomata are thought to be helpful in the study of plant self-protection responses under stress, but there are a few reports on the study of stomata at a genetic level. Meanwhile, most of the studies on patchy stomata are focused on trees and other plants [7,32], but there are a few studies on patchy stomata in crops. Further study of patchy stomata on crops may improve crop photosynthetic efficiency and thus increase yields [33].…”
Section: Discussionmentioning
confidence: 99%